2022
DOI: 10.3389/frph.2022.945351
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of sperm morphology in male infertility

Abstract: This brief report concerns the role of human sperm morphology assessment in different fields of male infertility: basic research, genetics, assisted reproduction technologies, oxidative stress. One of the best methods in studying sperm morphology is transmission electron microscopy (TEM) that enables defining the concept of sperm pathology and classifying alterations in non-systematic and systematic. Non-systematic sperm defects affect head and tail in variable ratio, whereas the rare systematic defects are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 123 publications
0
0
0
1
Order By: Relevance
“…The antioxidant treatment can have an ameliorative effect on the sperm morphology. Mounting evidence indicated that antioxidant treatments can improve sperm morphology by reducing oxidative stress and its detrimental effects on sperm [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant treatment can have an ameliorative effect on the sperm morphology. Mounting evidence indicated that antioxidant treatments can improve sperm morphology by reducing oxidative stress and its detrimental effects on sperm [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalitas spermatozoa yang mencapai 30-35% dapat mengakibatkan infertilitas. Lebih lanjut Moretti et al, (2022) melaporkan bahwa abnormalitas dapat menjadi penghambat keberhasilan fertilisasi jika persentasinya…”
Section: Abnormalitasunclassified